2019
DOI: 10.1097/mpg.0000000000002330
|View full text |Cite
|
Sign up to set email alerts
|

Variables Impacting the Time Taken to Wean Children From Enteral Tube Feeding to Oral Intake

Abstract: Objectives: This study investigated biological factors, which may influence the time taken for children to wean from enteral to oral intake. Methods: Retrospective case-note audit of 62 tube-fed children (nasogastric or percutaneous endoscopic gastrostomy) aged 6 months to 8 years, participating in an intensive tube weaning program. Program design included family-focused mealtimes, child autonomy, and appetite stimulation. A regression model was develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 26 publications
1
28
0
Order By: Relevance
“…Once parents realized enteral feeding would not be a quick fix, what mattered changed, from getting through a difficult but short period, to thriving despite the tube:
Early on you think this is temporary, done in a few weeks' time. Then nine months later, you are still there, so I need to work out and say, “What are we going to plan for the long term?”
This signals the importance of tube exit planning and other strategies that clarify the expected duration of tube feeding and the uncertainties that might surround this (Lively, McAllister, & Doeltgen, 2019; Syrmis et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Once parents realized enteral feeding would not be a quick fix, what mattered changed, from getting through a difficult but short period, to thriving despite the tube:
Early on you think this is temporary, done in a few weeks' time. Then nine months later, you are still there, so I need to work out and say, “What are we going to plan for the long term?”
This signals the importance of tube exit planning and other strategies that clarify the expected duration of tube feeding and the uncertainties that might surround this (Lively, McAllister, & Doeltgen, 2019; Syrmis et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Two rounds of coding were conducted, each of which involved multiple iterations to identify and refine themes, and followed MacQueen, This signals the importance of tube exit planning and other strategies that clarify the expected duration of tube feeding and the uncertainties that might surround this (Lively, McAllister, & Doeltgen, 2019;Syrmis et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Across the included studies, we identified 3 distinct approaches to intervention with the ultimate aim of tube weaning: (1) those grounded in behavioral strategies, 7–12,20,21,28,34,35,40 (2) those with a biomedical or other treatment focus, 17,27,39,41 and (3) those that followed a child‐ and family‐centered approach 13–16,18,19,22,24–26,29,36,37,42,43 …”
Section: Resultsmentioning
confidence: 99%
“…For example, some programs report on change in number of bites swallowed/mouth cleans 7,8 . Others evaluate changes in preweaning and postweaning weight or body mass index (BMI) in isolation 9–17 or in the context of changes in the child's behavior and feeding capacity 5,18–22 . Success rates may also depend on the specific definition of what it means to be weaned (no tube use) or not weaned (continuing tube use in some capacity) 23–26 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation